2006
DOI: 10.4049/jimmunol.177.5.3089
|View full text |Cite
|
Sign up to set email alerts
|

Early Immunization Induces Persistent Tumor-Infiltrating CD8+ T Cells against an Immunodominant Epitope and Promotes Lifelong Control of Pancreatic Tumor Progression in SV40 Tumor Antigen Transgenic Mice

Abstract: The ability to recruit the host’s CD8+ T lymphocytes (TCD8) against cancer is often limited by the development of peripheral tolerance toward the dominant tumor-associated Ags. Because multiple epitopes derived from a given tumor Ag (T Ag) can be targeted by TCD8, vaccine approaches should be directed toward those TCD8 that are more likely to survive under conditions of persistent Ag expression. In this study, we investigated the effect of peripheral tolerance on the endogenous TCD8 response toward two epitope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 59 publications
1
37
1
Order By: Relevance
“…A fourth epitope, designated epitope V, is immunorecessive and does not induce T CD8 unless the three dominant epitopes are inactivated (29). In previous studies using T Ag transgenic mice, we demonstrated that epitope Ispecific T CD8 are eliminated from the peripheral T cell repertoire more rapidly than T CD8 specific for epitope IV (8,9). In addition, immunization toward epitope IV can prevent the development of insulinomas in RT4 mice, although this approach fails to mediate the regression of established tumors (9).…”
Section: O Ne Obstacle To Successful Cd8mentioning
confidence: 99%
See 2 more Smart Citations
“…A fourth epitope, designated epitope V, is immunorecessive and does not induce T CD8 unless the three dominant epitopes are inactivated (29). In previous studies using T Ag transgenic mice, we demonstrated that epitope Ispecific T CD8 are eliminated from the peripheral T cell repertoire more rapidly than T CD8 specific for epitope IV (8,9). In addition, immunization toward epitope IV can prevent the development of insulinomas in RT4 mice, although this approach fails to mediate the regression of established tumors (9).…”
Section: O Ne Obstacle To Successful Cd8mentioning
confidence: 99%
“…In that study, however, the effect of such treatment on tumor progression was not investigated due to the slow onset of tumor appearance. Recently, we demonstrated that epitope I-specific T CD8 also are highly susceptible to peripheral tolerance in a different SV40 T Ag transgenic lineage, line RIP1-Tag4 (RT4) mice (9), which express SV40 T Ag as a transgene from the rat insulin promoter and develop insulinomas (24,25). T Ag expression begins around 5 wk of age in RT4 mice, leading to the development of islet hyperplasia by three months of age.…”
Section: O Ne Obstacle To Successful Cd8mentioning
confidence: 99%
See 1 more Smart Citation
“…In most Tg models, Tag is expressed by a strong tissue-specific promoter, resulting in early CTL tolerance. However, in some Tag-Tg mice, including mice developing sporadic tumors in a stochastic fashion, functional epitope IV-specific CTLs were retained (10,(13)(14)(15)(16).…”
mentioning
confidence: 99%
“…The elimination of CFSE-labeled target cells in spleen of recipients was analyzed after 18 h by flow cytometry. in vivo kill was calculated: percentage of specific killing ¼ (1-(ratio of control mice/ratio of immunized mice) Â 100), where the ratio is the percentage of CFSE low /CFSE high (Otahal et al, 2006).…”
Section: Histology and Immunohistochemistrymentioning
confidence: 99%